Edukasi Makanan Pendamping ASI (MP-ASI) Sebagai Upaya Pencegahan Stunting di Desa Ngumpul Kecamatan Jogoroto Jombang - Vivin Eka Rahmawati; Ninik Azizah; Lina Alfiyani; Luluk Nur Kholisoh (PPNI UNIMMAN, 2023)
Nutritional needs for babies are not only obtained from breast milk. Other nutritional needs can be obtained from complementary foods for breast milk complementary feeding. The condition of failure to thrive in children under five is caused by a lack of nutritional intake for a long time and the occurrence of recurrent infections and these two causal factors are influenced by inadequate parenting patterns, especially in the 1000 HPK. This community service activity takes the form of outreach using complementary feeding and stunting leaflets which is carried out using a question and answer discussion method to the target of the outreach. Activities are divided into 3 stages, namely preparation, implementation and evaluation stages. The targets for this activity are 25 mothers who have toddlers aged 6-24 months in Ngumpul Jogoroto Village, Jombang on June 5 2023. The tool used in this activity is leaflets. This community service program increases public knowledge about good and healthy complementary feeding to meet nutritional needs and prevent stunting.